2018
DOI: 10.3357/amhp.4887.2018
|View full text |Cite
|
Sign up to set email alerts
|

Protective Knee Braces and the Biomechanics of the Half-Squat Parachute Landing

et al.

Abstract: The elastic and semi-rigid knee braces both effectively restricted motion stability of the knee joint in the sagittal and coronal planes. The semi-rigid brace had a more marked effect, although the comfort of this device should be improved.Wu D, Zheng C, Wu J, Wang L, Wei X, Wang L. Protective knee braces and the biomechanics of the half-squat parachute landing. Aerosp Med Hum Perform. 2018; 89(1):26-31.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 0 publications
0
33
0
2
Order By: Relevance
“…In Britain, Australia, Germany, and other developed countries, internal ankle support was widely used by paratroopers as necessary protective equipment [2,8,16]. Although air-filled ankle braces, EVC foam braces, and high-elastic-fiber ankle socks had been developed successively in China, no relevant report exists on whether or not they can effectively prevent ankle injuries [2,3,5,17]. According to the epidemiological survey and preliminary biomechanical research conducted for this study, the injury mechanism was found to be excessive dorsiflexion and inversion of the ankle joint during HSPL, and it was also found that wearing ankle braces can effectively restrict ankle joint motion stability on the sagittal and coronal planes [2,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Britain, Australia, Germany, and other developed countries, internal ankle support was widely used by paratroopers as necessary protective equipment [2,8,16]. Although air-filled ankle braces, EVC foam braces, and high-elastic-fiber ankle socks had been developed successively in China, no relevant report exists on whether or not they can effectively prevent ankle injuries [2,3,5,17]. According to the epidemiological survey and preliminary biomechanical research conducted for this study, the injury mechanism was found to be excessive dorsiflexion and inversion of the ankle joint during HSPL, and it was also found that wearing ankle braces can effectively restrict ankle joint motion stability on the sagittal and coronal planes [2,5].…”
Section: Discussionmentioning
confidence: 99%
“…Landing injuries are the most frequent of all parachuting injuries and ankle joint injuries are the most common landing injury [1]. The half-squat parachute landing (HSPL) posture has been adopted by Chinese paratroops [2,3]. When compared with the sideways roll parachute landing fall, the HSPL method may reduce the probability of asynchronous landings on either the left or right foot [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudios más recientes, como el realizado por Wu y otros (Wu et al, 2018), encontraron que al usar un brace de rodilla (un dispositivo para estabilizar la articulación y no cargarla en fases de aterrizaje) la disminución de las fuerzas de reacción (FRP), medidas con una plataforma de fuerza a diferentes alturas, no fueron estadísticamente significativas. Para este estudio se usaron diferentes tipos de brace, cada uno con una rigidez diferente.…”
Section: Marco Teóricounclassified
“…Therefore, [12] made a study about the use of ankle braces to avoid the injuries which will also reduce the budget cost of hospitalisation. In addition, ACL injury at the knee joint regularly happened when parachutists bent over during landing, hence [13] suggested the use of semi-rigid knee brace to reduce knee injuries. A good technique during landing is called "prepare to land attitude" where the flexion of ankles and knees must be less than 45 • and the knee flexion must not exceed 130 • to avoid ACL injury [10].…”
Section: Introductionmentioning
confidence: 99%